The Elements of Comedy and Parody in the Dionysiaca of Nonnus - Lasek, Anna Maria (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
In this article the author presents the elements of comedy and parody in the Dionysiaca of Nonnus. The analysis of the passages excerpted from the Dionysiaka shows that the composition of Nonnus’ poem is based on the principle of generic variety.